The Particular Baptist Fund and Its Deputations to Suffolk, 1841–1898. (3rd July 2017) - Grass, Tim
ABSTRACT: In an attempt to improve its acquaintance with the needs and opportunities of ministers and churches which it assisted, the Particular Baptist Fund instituted a system of deputation visits to different parts of England. The ministers making these visits recorded their impressions in reports submitted to the managers of the fund. These represent a hitherto-unused source of theologically aware and candid impressions of Baptist congregational life. This article examines the reports covering visits made to churches and ministers in Suffolk. It argues that these demonstrate that the divide between the Baptist Union and the newly formed Strict and Particular Baptist association in Suffolk was by no means fixed, and that both streams of churches in the county saw themselves as belonging to the same Particular Baptist tradition. Nevertheless, the deputations frequently took issue with the high Calvinism of many of the rural Suffolk churches.